Diseño Arquitectónico de un centro geriatrico residencial en la ciudad de Ibarra - Castillo Acero, Karla Ginella (2024)
The main purpose of this thesis work is to design a residential geriatric center in the city of Iba rra, province of Imbabura, focusing on the needs of the local elderly population. The methodological approach adopted c onsisted of collecting information to evaluate the conditions of existing care centers for the eld erly and determine the challenges faced. In addition, a site analysis was carried out through a diagnosis to identify the needs and requirements of the vulnerable population. Once the challe nges were identified, an attempt was made to develop a functional architectural proposal by i mplementing the technical regulations for the creation of residential centers for the elderly.